A Viewpoint on the Leaky Gut Syndrome to Treat Allergic Asthma: A Novel Opinion - Masoumeh Kaboli Farshchi PhD; Farahzad Jabbari Azad MD; Roshanak Salari PharmD, PhD; Majid Mirsadraee MD; Majid Anushiravani MD, PhD (SAGE Publishing, 2017)
Asthma is a common respiratory disease characterized by airway inflammation, airway hyperreactivity, and reversible airflow obstruction. Despite current treatments, the prevalence of asthma has increased markedly over decades. According to the theories proposed to explain the pathophysiology of autoimmune diseases in integrative medicine, leaky gut syndrome is a phenomenon of increased intestinal permeability due to the disruption of tight junctions and is thought to be related to many chronic diseases, such as food intolerance, inflammatory bowel disease, rheumatoid arthritis, asthma, and other autoimmune disease. One of the classical approaches used by integrative physicians to treat leaky gut syndrome is to repair intestinal permeability to prevent allergic cascade. Due to several mechanisms that have been mentioned in the protective effects of plant gums and plantain family seeds on the intestinal epithelium, we can propose an effective management for leaky gut syndrome to treat asthma.